The Effect of Alfha Angle Variation Sudu Rotor Blade On Wind Turbine Performance Using Blade NACA 0018 - Habibullah; Rachmad Firdaus (Universitas Muhammadiyah Sidoarjo, 2021)
Indonesia currently has a growing need for energy, this will experience an energy crisis condition, dependence on fossil fuels will at least pose a serious threat, therefore there must be alternative energy as a substitute and reserves such as wind energy, water energy, solar energy, and other. Because Indonesia has abundant water sources, with this my research intends to develop water as a renewable energy source that can be used as a source of energy for hydroelectric power plants or also called water turbines. The water turbine is an early generator that uses the potential energy of water to become mechanical energy where the water turns the turbine wheel. This study aims to determine the effect of the number of blades, the effect of the profile, the effect of rotor blade wing tip, Naca 0018, and the resulting energy efficiency. This research uses experimental research type.